1996
DOI: 10.1051/aas:1996313
|View full text |Cite
|
Sign up to set email alerts
|

Detection of structures on multiple scales around the South Galactic Pole

Abstract: Abstract. -We report the results of a 2D analysis of distributions of galaxies in a search for structures on a wide range of scales, from clusters up to superclusters and beyond, including the identification of voids. The structures are identified in data from the COSMOS/UKST Southern Sky Galaxy Catalogue (CUSSGC). The subsample used in this first investigation contains some 1.4 10 6 galaxies in an area of ∼ 69 × 44 degrees around the South Galactic Pole. From our analysis, we find 25 very large-scale structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…One method of decomposing images into different physical scales is with the wavelet transform . This tool has been widely used in astronomy for purposes such as de-noising images , analysing the clustering of galaxies (Slezak et al 1993;Escalera & MacGillivray 1995;Martínez et al 2005) and detecting non-Gaussianity in the Cosmic Microwave Background Note-The depth is measured in randomly positioned 0.4 ′′ circular apertures in the original reduced images.…”
Section: Wavelet Decompositionmentioning
confidence: 99%
“…One method of decomposing images into different physical scales is with the wavelet transform . This tool has been widely used in astronomy for purposes such as de-noising images , analysing the clustering of galaxies (Slezak et al 1993;Escalera & MacGillivray 1995;Martínez et al 2005) and detecting non-Gaussianity in the Cosmic Microwave Background Note-The depth is measured in randomly positioned 0.4 ′′ circular apertures in the original reduced images.…”
Section: Wavelet Decompositionmentioning
confidence: 99%
“…For denoising and deconvolution, wavelets have also demonstrated how powerful they are for discriminating signal from noise (Starck et al, 2002b). In cosmology, wavelets have been used in many studies such as for analyzing the spatial distribution of galaxies (Slezak et al, 1993;Escalera and MacGillivray, 1995;Starck et al, 2005a;Martinez et al, 2005), determining the topology of the universe (Rocha et al, 2004), detecting non-Gaussianity in the CMB maps (Aghanim and Forni, 1999;Barreiro et al, 2001;Vielva et al, 2004;Starck et al, 2004), reconstructing the primordial power spectrum (Mukherjee and Wang, 2003), measuring the galaxy power spectrum (Fang and Feng, 2000) or reconstructing weak lensing mass maps (Starck et al, 2005b). It has also been shown that noise is a problem of major concern for N-body simulations of structure formation in the early Universe and that using wavelets to remove noise from N-body simulations is equivalent to simulations with two orders of magnitude more particles (Romeo et al, 2003(Romeo et al, , 2004.…”
Section: Wavelets In Astronomymentioning
confidence: 99%
“…Structures of galaxies: Only a few catalogs of clusters [20,10,13] and compact groups [25] are based upon automatically selected galaxy samples, which happen to be optical and photographic (hence subject to photometric non-linearities). Because star formation is probably enhanced by galaxy interactions, one expects that the statistical properties of pairs, groups and clusters of galaxies built from NIR selected galaxy catalogs will be different from those built from optical catalogs.…”
Section: Extragalactic Research and Cosmologymentioning
confidence: 99%